Management of oesophageal atresia in a developing country: Is primary repair forbidden? - Samuel Osei-Nketiah; Afua A. J. Hesse; William Appeadu-Mensah; Hope Glover-Addy; Victor K Etwire; Pokua Sarpong (Wolters Kluwer Medknow Publications, 2016)
Background: The aim of the study was to evaluate the outcomes of initial surgical procedures for oesophageal atresia at our institution. Primary repair of oesophageal atresia at our centre was perceived to be associated with a high mortality rate. In view of this, almost all patients seen since January 2014 were offered initial surgery for staged repair. Materials and Methods: A retrospective review of records of infants with oesophageal atresia seen at the centre from January 2007 to December 2014 was used in this study. Results: Eighty-five cases of oesophageal atresia were seen over the study period. Of these, 74 (87.1) had surgery performed. Surgical outcome was, however, indicated in 67 of the 74, with overall survival rate of 40.3%. Among the 67 patients, early primary repair was performed in 24 (35.8%) with a survival rate of 45.8% (11 patients). Totally, 12 (17.9%) of the 67 had initial procedure for delayed primary repair, with a survival rate of 16.7% (2 patients). The remaining 31 (46.3%) patients had initial surgery for staged repair, with survival rate of 45.2% (14 patients). There was no association between the type of surgery and the surgical outcome (χ2 = 3.396, df = 2, P = 0.183). Conclusion: The overall surgical survival rate of 40.3% for oesophageal atresia at our institution is low. This study did not show any difference in the survival rate of 45.8% and 45.2% associated with primary repair and staged repair respectively.